PRODUCTION OF AMYLOCELLULOLYTIC ENZYMES AND THEIR VIABILITY ON CARRIER MEDIA BY Bacillus sp. U4 AND Pseudomonas sp. U3 - Enny Zulaika; Salma Shavira Rahma Khofifah (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Amylase and cellulase are enzymes that are amyocellulolytic. Both are extracellular enzymes that can degrade organic materials, namely starch and cellulose. The purpose of this study was to determine whether Bacillus sp. U4 and Pseudomonas sp. U3 could produce amylocellulolytic enzymes and determine their viability after being incubated for 2 hours on the husk, peat, and sawdust carrier media. Screening for the presence of amylase was carried out on a selective medium, namely nutrient agar-amylum 0.5 %, and cellulase on carboxymethyl cellulose-agar medium. Both isolates were inoculated into sawdust, husk, peat carrier media and incubated for 2 hours. Viability was observed using the total plate count method. Bacillus sp. U4 and Pseudomonas sp. U3 can produce amylase and cellulase. The best isolate viability after incubation for 2 hours was found in husk carrier media with 2.13 x 105 CFU/gr of husk media.